Becoming a Tempered Radical: Student Affairs Administrators as Advocates for LGBTQ Students at Eight Higher Education Institutions in the South. Issue 4 (2nd October 2019) - Broadhurst, Christopher; Martin, Georgianna
Abstract: This narrative study examines how student affairs administrators in eight institutions in the southern United States became change agents in higher education for LGBTQ students. Participants shared stories of their identity development, turning points about needs of LGBTQ students, and their choice to advocate in higher education. Implications for practice in higher education and student affairs are discussed.